2021
DOI: 10.1002/joc.7368
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of seasonal precipitation dynamics over the North‐West Himalayan region under future warming scenarios

Abstract: In the context of widely reported climate change over the mountainous region, the present work addresses the notable changes in the seasonal precipitation dynamics over the NWH region under two different future warming scenarios [socioeconomic pathway 245 (SSP245) and socio economic pathway 585 (SSP585)]. Using three coupled climate models which participated in the Climate Model Inter‐comparison Project Phase 6 (CMIP6), we focus on the alterations of the spatio‐temporal pattern of solid and liquid precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 108 publications
(120 reference statements)
2
2
0
Order By: Relevance
“…In Exp02, the temperature of the whole atmosphere increased (Figure 8a); however, in Exp03, the temperature only increased in the lower atmosphere (Figure 8b). Banerjee and Singh [44] also drew the cross sections of the differences (SSP5-8.5 minus Historical) in temperature, and the results indicated that the temperature increased in the whole atmosphere, which was consistent with our conclusion. Therefore, we thought that the warming-induced increases (Exp02 minus Exp01) in the temperature of the whole atmosphere were reasonable.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Exp02, the temperature of the whole atmosphere increased (Figure 8a); however, in Exp03, the temperature only increased in the lower atmosphere (Figure 8b). Banerjee and Singh [44] also drew the cross sections of the differences (SSP5-8.5 minus Historical) in temperature, and the results indicated that the temperature increased in the whole atmosphere, which was consistent with our conclusion. Therefore, we thought that the warming-induced increases (Exp02 minus Exp01) in the temperature of the whole atmosphere were reasonable.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the warming in Exp03 was only driven by decreasing surface upward longwave radiation, and then the temperature only increased in the lower atmosphere (discussed later). Based on the high emission scenario (SSP5-8.5), the future temperature increased in the whole atmosphere [44], which was consistent with our conclusion in Exp02 (Figure 8a). In this study, the whole atmosphere referred to 0-12km and mainly located in troposphere.…”
Section: The Warming Experiments By Increasing Surface Energysupporting
confidence: 90%
“…Studies based on CMIP5 and CMIP6 model output have agreed that higher elevations are very likely to receive significantly more precipitation in a warmer climate, with insignificant drying in the foothills, and increased rainfall over the northern Indian plains (Almazroui et al, 2020;Banerjee and Singh, 2022). Banerjee and Singh (2022) also found a shift in precipitation seasonality, with the peak snowfall month moving from February to March by the end of the 21st century.…”
Section: Changing Impactsmentioning
confidence: 98%
“…The variables are ensemble members of ‘atmospheric realm ’, the parent variant label is ‘ r1i1p1f1 ’ and the parent experiment ids are ‘ piControl ’. Another criterion for the selection of the models is the observations and recommendations of the previous research works (Banerjee and Singh, 2021; Kundu et al, 2021; Kundu & Singh, 2020; Menon et al, 2013; Sabeerali et al, 2012; Singh et al, 2017; Singh et al 2018a; Singh et al, 2018b; Singh, 2023). Table 1 illustrates the description of the 12 CMIP6 models selected for the study.…”
Section: Datasets Usedmentioning
confidence: 99%